Spatially structured relationships between white banana prawn (Penaeus merguiensis) catch and riverine flow in the Northern Prawn Fishery, Australia. (1st October 2022) - Turschwell, Mischa P.; Stewart-Koster, Ben; Kenyon, Rob; Deng, Roy A.; Stratford, Danial; Hughes, Justin D.; Pollino, Carmel A.
Abstract: Water resource development can lead to the significant alteration of natural flow regimes, which can have impacts on the many aquatic species that rely on both freshwater and estuarine environments to successfully complete their lifecycles. In tropical northern Australia, annual catches of commercially harvested white banana prawns (WBP) are highly variable in response to environmental conditions, namely rainfall and subsequent riverine flow. However, little is known about the spatial extent to which flow from individual rivers influences offshore WBP catch. In this study, we quantify how the relationship between WBP catch in the Gulf of Carpentaria is influenced by flow from the Mitchell River, Queensland Australia. We used a Bayesian framework to model both prawn presence and catch per unit effort, and found evidence that multiple components of the flow regime contribute to fishery catch. We also found evidence to suggest that the relationships between prawn presence and flow were spatially structured across the fishing ground. Our results suggest that attributing fishery catch to a single river remains challenging, though highlights the importance of maintaining natural flow regimes to support a highly valuable commercial fishery species in the face of potential water resource development. Highlights: Water resource development threatens natural flow regimes. We modelled how riverine flow influences a highly valuable prawn fishery. Multiple aspects of the flow regime were important for fishery catch. Relationships between catch and flow were spatially structured in the fishery. Our results inform management of ecosystems threatened by hydrologic development.